Optimization of Column Stirrup Selection (Square and Spiral) for Earthquake Resistance of 10-Storey Buildings - Khairunnisa, Syahla; Amalia; Saputra, Jonathan (UKaRsT, 2024)
Earthquake-resistant building design is very important, especially in earthquake-prone areas such as Indonesia. The shape of the column cross-section and the ties' configuration greatly affect the building's stiffness when exposed to earthquake loads. Therefore, knowing the optimal tie configuration to increase earthquake resistance is important. This study aims to analyze the structural performance of a 10-story building using columns with spiral stirrups and square stirrups. Model 1 uses columns with square stirrups, Model 2 uses spiral stirrups, and Model 3 is a combination of both. Simulations were conducted using ETABS 18 software, where the base shear force, displacement, and inter-story drift as well as the collapse pattern and performance level of the structure were analyzed using the pushover analysis method to determine the effect of each configuration on the stiffness and ductility of the columns when receiving earthquake loads. Analysis of Variance (ANOVA) analysis was carried out to ensure that the differences in seismic performance between the three models were significantly validated. The results show that Model 2 has lower displacement and base shear force values and smaller inter-story drift than the other models, and the collapse pattern and structural performance level of Model 2 are also smaller than the other models. The ANOVA results showed no significant difference between the models. This is because the differences in displacement and drift values are relatively small. These findings can provide guidance for selecting the most efficient column tie configuration for resisting earthquake loads and achieving safety levels.